Partisipasi Masyarakat dalam Musyawarah Perencanaan Pembangunan di Kota Kendari - Salahuddin, Salahuddin (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2012)
The research aimed to identify the community participation in the implementation of development planning deliberation. The research method used is combined with methods (mixed methods). The sample interviewed in the quantitative approach was as many as 60 people and informants who were interviewed in-depth qualitative approach as many as 16 people. The results showed that the community participation in the implementation of development planning deliberation has been going well. Implementation of development planning deliberation has met most of the elements of community participation were examined.